CIFOR’s experience with research partnership: responding to the new research challenges - Turnbull, J.W.; Byron, R.N. (FORSPA, 1998)
The Center for International Forestry Research (CIFOR) has adopted an interdisciplinary, complex-systems approach to address both scientific and capacity-building challenges in forestry. Its strategic research agenda on tropical forests is implemented primarily through collaborative partnerships. The differences between 'collaboration, 'cooperation' and coordination' is stressed with the latter generally describing lower levels of interactions between scientists and are often the precursors of collaboration. The nature and duration of the research partnerships reflect the specific research problems being addressed but include scientists from government forestry agencies, universities, non-government organisations and the private sector in both developed and developing countries. The benefits and inhibitors of collaborative research arrangements compared with competitive forestry research are discussed. CIFOR's partnership arrangements are categorised according to the degree of involvement of the CIFOR scientists and the extent of financial contributions made to partners. Examples of each of the four partnership models are given. The capacity building aspects off CIFOR's collaborative partnerships are discussed, particularly the 'learning by doing', which is the main vehicle by which training is conducted.